Implementasi Nilai-Nilai Prophetic Untuk Membentuk Karekter Siswa SMA Negeri 7 Yogyakarta - Rahayu, Nur Ellyanawati Esty (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2023)
The purpose of this study is to determine the character building of students of SMA Negeri 7 Yogyakarta through the application of prophetic values. The researcher's approach is descriptive-qualitative. Data sources are obtained from primary data sources, namely 1) in-depth interviews with the principal, deputy head of curriculum, religion teacher, counseling guidance teacher, student council chairman and Rokhis chairman; 2). Observation, namely directly observing student character building activities using prophetic values; and secondary data sources, namely the results of reports on religious activities and character building. The results of the study explain that the application of prophetic values in SMA Negeri 7 Yogyakarta shapes student character: 1) Building a 5S culture (smiling, greeting, polite and courteous); 2) Building IMTAQ (Faith and Taqwa) culture; and 3) application of prophetic values (in learning activities and projects).